Health-related quality of life and patient-centred outcomes with COVID-19 vaccination in patients with breast cancer and gynaecological malignancies - Forster, Marie; Wuerstlein, Rachel; Koenig, Alexander; Stefan, Alexandra; Wiegershausen, Elisa; Batz, Falk; Trillsch, Fabian; Mahner, Sven; Harbeck, Nadia; Chelariu-Raicu, Anca (Frontiers in Oncology, 2023)
Introduction: Safety and tolerability of COVID-19 vaccines were demonstrated by several clinical trials which led to the first FDA/EMA approvals in 2021. Because of mass immunizations, most social restrictions were waived with effects on quality of life. Therefore, our a-priori hypothesis was that COVID-19 vaccination impacted the health-related quality of life (HR-QoL) in patients with breast and gynecological cancer. Methods: From March 15 th until August 11 th , 2022, fully vaccinated patients with breast and gynecological cancer treated in the oncological outpatient clinics of the